Web-based personal study helper based on lesson plan using gamification / Ahmad Taqiyuddin Mohd Zahrin, Fadzlin Ahmadon and Khairul Nurmazianna Ismail - Mohd Zahrin, Ahmad Taqiyuddin; Ahmadon, Fadzlin; Ismail, Khairul Nurmazianna (College of Computing, Informatics, and Mathematics, 2024)
Study is defined as the activity or process of learning by reading, memorising facts, attending school, etc. To study effectively, students need to have aids that facilitate their learning process. With technology nowadays, students can use many applications as aids or study tools. However, not all students have the same motivation to learn, which might result in low academic achievement. Students also disengage during their classes and have difficulty understanding the interconnections between concepts. To address these challenges, the research project aims to develop web-based personal study helpers with gamification elements to enhance student engagement, motivation, and comprehension of academic content. Gamification is the use of game elements such as badges, achievements, levels, points, and progress to make learning more interactive. The development project also has a generated mind map for note-taking as the visualisation aids in learning. This project also makes use of the traffic light colour code system for the pending assessment tracking for the students. This project follows the Modified Waterfall Model as its Software Development Life Cycle (SDLC), which has four phases: requirement analysis, design, implementation, and testing. To test the usability of the developed project, it used the System Usability Scale (SUS) questionnaire given to the UiTM students. The result of the SUS score for this project is 64.64, which indicates a moderate level of usability. In conclusion, the gamification elements, generated mind maps, and use of a traffic light colour code system for a pending assessment tracker have been successfully implemented in a web-based application, with all the functionality working as intended. By implementing gamification, this application also successfully increases the engagement of the students and enhances their learning experience.